Cancer Epigenetics: New Therapies and New Challenges. (26th February 2013) - Hatzimichael, Eleftheria; Crook, Tim
Abstract : Cancer is nowadays considered to be both a genetic and an epigenetic disease. The most well studied epigenetic modification in humans is DNA methylation; however it becomes increasingly acknowledged that DNA methylation does not work alone, but rather is linked to other modifications, such as histone modifications. Epigenetic abnormalities are reversible and as a result novel therapies that work by reversing epigenetic effects are being increasingly explored. The biggest clinical impact of epigenetic modifying agents in neoplastic disorders thus far has been in haematological malignancies, and the efficacy of DNMT inhibitors and HDAC inhibitors in blood cancers clearly attests to the principle that therapeutic modification of the cancer cell epigenome can produce clinical benefit. This paper will discuss the most well studied epigenetic modifications and how these are linked to cancer, will give a brief overview of the clinical use of epigenetics as biomarkers, and will focus in more detail on epigenetic drugs and their use in solid and blood cancers.